Debasing the voice: Subversive vocality in Harmony Korine's Trash Humpers. Issue 1 (1st June 2012) - Inouye, Shaun
Harmony Korine, one-time enfant terrible of the American cinema, returns to infamy with the uncategorizable Trash Humpers (2009), a 'found footage'-style, faux home-movie that documents the abhorrent acts of four sociopathic 'elders' in the nondescript suburbs of the American South. It is a film that has garnered attention due to its goading amateur aesthetic (the film is shot on VHS and purportedly edited on two VCRs), non-narrative approach and pro-filmic oddities, including the titular characters literally humping trash while donning lifelike geriatric masks. However, despite its arresting and oft-perplexing visual content, it is the film's unusual treatment of the soundtrack – or more specifically, the voice – that intimates meaning beyond mere provocation. Drawing on Michel Chion's theories of vocal disembodiment in the cinema, as well as Korine's continued remarks on the film's childhood origins, this article proposes that by intentionally decoupling the voice from the body and divesting it of its linguistic capabilities, Trash Humpers presents a version of vocality regressed to a pre-lingual state, before its ideological subjugation to the body through language. This, in turn, informs the childlike rendering of the trash humpers, who seem to revel in libidinal fixations of the past. By utilizing the voice as a non-verbal, autonomous entity, Trash Humpers demonstrates the voice's capacity to incite meaning outside the image, and furthers Korine's stature as a boundary pushing film-maker.